Malignant Rhabdoid Tumor of the Kidney in an 11-Month-Old Child: Case Report and Literature Review - Lopes, Laura Mendes; Grenteski, Fabricio; Naufel Júnior , Carlos Roberto; Coelho, Guilherme Andrade; Furlan, Guilherme Ferrarini; Tefilli, Nertan; Feitoza , José Anderson; Peixoto, Igor Luna (Brazilian Journal of Case Reports, 2024)
Malignant renal tumors represent about 6% of childhood tumors, with rhabdoid tumors (RT) being rare, accounting for approximately 2% of pediatric renal tumors. These tumors are notoriously aggressive, with a five-year survival rate of only 22%, and are often diagnosed at a metastatic stage. RT is associated with mutations in the SMARCB1 gene, but recent studies have identified relevant epigenetic characteristics. Treatment approaches include radiotherapy, chemotherapy, and surgery. Despite significant advancements in understanding these tumors in recent years, RT still presents considerable challenges in terms of treatment and prognosis, which remains poor. This case describes an atypical presentation of invasion and tumor expansion in a rare pediatric renal tumor, resulting in alterations in the patient's venous drainage, a condition that has not been previously documented in the literature.